Do handgrip strength and dexterity predict respiratory function in neuromuscular disease - YILDIZ ÖZER, AYSEL (My University, 2022)
Background Neuromuscular diseases are acquired or inherited diseases that affect the function of the muscles in our body, including respiratory muscles.Objective We aimed to discover more cost-effective and practical tools to predict respiratory function status, which causes serious problems with patients with neuromuscular disease. Methods The Vignos and Brooke Upper Extremity Functional Scales were used to evaluate functional status for patient recruitment. The handgrip strength and dexterity of patients were measured using a dynamometer and nine-hole peg test. Respiratory function parameters: forced vital capacity, forced expiratory volume in one second, and peak expiratory flow were evaluated using spirometry. Results The mean age of the 30 patients was 11.5 +/- 3.79 years old. Significant relationships were found between nine-hole-peg-test scores and respiratory function parameters on both sides. Significant correlations were found between both handgrip strength and respiratory function parameters ( p < 0.05). In the linear regression analysis, it was seen that the forced expiratory volume in 1 second, and peak expiratory flow values could be explained in different percentages ( p < 0.05). Conclusions Handgrip strength and dexterity measurements can be used as indicators for estimating respiratory function parameters in terms of cost and accessibility, although it is known that they will not replace respiratory function tests.

Antecedentes As doenças neuromusculares são doenças adquiridas ou hereditárias que afetam a função dos músculos do nosso corpo, incluindo os músculos respiratórios. Objetivo Nosso objetivo foi descobrir ferramentas mais práticas e econômicas para prever o estado da função respiratória, que causa sérios problemas em pacientes com doença neuromuscular. Métodos As Escalas Funcionais da Extremidade Superior de Vignos e Brooke foram utilizadas para avaliar o estado funcional para recrutamento de pacientes. A força de preensão manual e a destreza dos pacientes foram medidas por meio de um dinamômetro e do teste de nove buracos. Os parâmetros da função respiratória: capacidade vital forçada, volume expiratório forçado no primeiro segundo e pico de fluxo expiratório foram avaliados por meio da espirometria. Resultados A média de idade dos 30 pacientes foi de 11,5 3,79 anos. Relações significativas foram encontradas entre as pontuações do teste de nove buracos e os parâmetros da função respiratória em ambos os lados. Correlações significativas foram encontradas entre a força de preensão manual e os parâmetros da função respiratória (p < 0,05). Na análise de regressão linear, observou-se que o volume expiratório forçado no primeiro segundo e os valores de pico de fluxo expiratório puderam ser explicados em diferentes percentuais (p < 0,05). Conclusões As medidas de força de preensão manual e destreza podem ser utilizadas como indicadores para estimar parâmetros da função respiratória em termos de custo e acessibilidade, embora se saiba que não substituirão os testes de função respiratória.
A força de preensão manual e a destreza predizem a função respiratória em doenças neuromusculares
Keywords: Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Life Sciences; Health Sciences; Natural Sciences; SİNİR BİLİMİ; Sinirbilim ve Davranış; Yaşam Bilimleri (LIFE); Psikiyatri; Klinik Tıp (MED); NEUROSCIENCES; NEUROSCIENCE & BEHAVIOR; Life Sciences (LIFE); PSYCHIATRY; Clinical Medicine (MED); Psikiyatrik Ruh Sağlığı; Duyusal Sistemler; Gelişimsel Sinirbilim; Bilişsel Sinirbilim; Hücresel ve Moleküler Sinirbilim; Sinirbilim (çeşitli); Genel Sinirbilim; Psikiyatri ve Ruh Sağlığı; İnsan Bilgisayar Etkileşimi; Fizik Bilimleri; Psychiatric Mental Health; Sensory Systems; Developmental Neuroscience; Cognitive Neuroscience; Cellular and Molecular Neuroscience; Neuroscience (miscellaneous); General Neuroscience; Psychiatry and Mental Health; Human-Computer Interaction; Physical Sciences; Neuromuscular Diseases; Motor Skills; Respiratory Function Tests; Hand Strength; DUCHENNE MUSCULAR-DYSTROPHY; 9-HOLE PEG TEST; GRIP STRENGTH; PULMONARY-FUNCTION; EGEN KLASSIFIKATION; STANDARDIZATION; PARAMETERS; FATIGUE; SCORES; ADULTS; Doenças Neuromusculares; Destreza Motora; Testes de Função Respiratória; Força da Mão; Neuromuscular Diseases; Motor Skills; Respiratory Function Tests; Hand Strength